The Topicality of the Difference Thesis - Merz, Martina (Technische Universität Dortmund, 2006)
Within science and technology studies, constructivism has never existed as a single variant but under alternative interpretations. In this article it is argued that the different variants have maintained their topicality in unequal measure. It focuses on two variants of constructivism: The first emphasizes the isomorphism of scientific and other practices and insists that there are no epistemic particularities in scientific knowledge production ('analogy approach'); the second accounts for the success of contemporary science by relating it to the specifics of scientific laboratories ('difference approach'). In this paper it is argued that the second variant can provide a set of challenging research problems that have not, to date, been sufficiently addressed in the literature. The problems center on the relation between laboratories and contexts of application, as well as on the concept of the laboratory and its possible extensions. In contrast, the issues associated with the analogy approach have been well explored in previous bodies of work. This article develops a research agenda for a constructivist account of knowledge production that may be employed within other discourses in the social sciences.s
Revisiting Constructivism and the Laboratory
Science, Technology & Innovation Studies
Keywords: 300; 330